2018
DOI: 10.1159/000494371
|View full text |Cite
|
Sign up to set email alerts
|

Primary Human Neutrophils Exhibit a Unique HIV-Directed Antibody-Dependent Phagocytosis Profile

Abstract: The only clinical HIV vaccine trial to demonstrate efficacy, RV144, correlated protection with the antibodies (Abs) mediating function via the “constant” immunoglobulin region, the crystallizable fragment (Fc). These data have supported a focus on the induction of Abs by vaccines that trigger antiviral activities by relevant leukocytes via Fc receptors (FcRs). Neutrophils are phagocytes that comprise > 50% of leukocytes and display unique FcRs. We sought to compare the Ab-dependent cellular phagocytosis (ADCP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Current literature suggests that recognition of antigen-antibody complexes by neutrophils may be important in eliciting various effector responses. The removal of pathogens by neutrophils can occur directly in a process termed antibody-dependent neutrophil phagocytosis (ADNP) in which neutrophils recognize pathogen-antibody immune complexes 17,18 , or through NETosis, a specialized cell death program in which neutrophils release neutrophil extracellular traps (NETs) consisting of chromatin modified with anti-microbial proteins 19,20 . In the context of various pathologies such as viral infection, cancer, and heparin-induced thrombocytopenia, NETosis has been shown to be largely driven by antibody-Fc receptor interactions which can be further regulated by antibody isotype and glycosylation profile [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Current literature suggests that recognition of antigen-antibody complexes by neutrophils may be important in eliciting various effector responses. The removal of pathogens by neutrophils can occur directly in a process termed antibody-dependent neutrophil phagocytosis (ADNP) in which neutrophils recognize pathogen-antibody immune complexes 17,18 , or through NETosis, a specialized cell death program in which neutrophils release neutrophil extracellular traps (NETs) consisting of chromatin modified with anti-microbial proteins 19,20 . In the context of various pathologies such as viral infection, cancer, and heparin-induced thrombocytopenia, NETosis has been shown to be largely driven by antibody-Fc receptor interactions which can be further regulated by antibody isotype and glycosylation profile [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, depending on the route of immunization, two different kinds of phagocytosis were important, mediated either by monocytes or neutrophils. Neutrophil-mediated phagocytosis has only recently explored in HIV infection using HIV-specific antibodies [49,50], and has shown distinct phagocytic outcomes to monocytes. This indicates the importance of exploring Fc effector functions in a wider variety of cell types than those routinely used.…”
Section: Discovering New Fc Effector Functions and Expanding Mechanismsmentioning
confidence: 99%
“…The widely accepted belief is that phagocytosis is most effective for killing microorganisms (e.g., bacteria), while the adaptive immune defense , mainly by lymphocytes, is more important for viral infections. However, increasing evidence has shown that phagocytosis plays a crucial role in killing a variety of intracellular or cytoplasmic viruses ranging from influenza, mumps, measles and rhinovirus to Ebola and HIV, either directly protecting against viral infections in the innate immune defence [ 20 , 21 , 22 , 23 , 24 , 25 ] or through the antibody-dependent cellular phagocytosis providing mechanisms for clearance of virus and virus-infected cells and for stimulation of downstream adaptive immune responses by antigen presentation or the secretion of inflammatory mediators [ 26 , 27 , 28 ]. Particularly in humoral (adaptive) immunity, B cells upon activation produce antibodies, each of which recognizes a unique antigen and neutralizes a specific pathogen.…”
Section: Introductionmentioning
confidence: 99%